Radio Galaxy Zoo: Discovery of a poor cluster through a giant wide-angle tail radio galaxy - Banfield, J.; Andernach, H.; Kapinska, A.; Rudnick, L.; Hardcastle, M.; Cotter, G.; Vaughan, S.; Jones, T.; Heywood, I.; Wing, J.; Wong, O.; Matorny, T.; et al. (Oxford University Press, 2016)
© 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society. We have discovered a previously unreported poor cluster of galaxies (RGZ-CL J0823.2+0333) through an unusual giant wide-angle tail radio galaxy found in the Radio Galaxy Zoo project. We obtained a spectroscopic redshift of z = 0.0897 for the E0-type host galaxy, 2MASX J08231289+0333016, leading to Mr = −22.6 and a 1.4 GHz radio luminosity density of L1.4 = 5.5 × 1024 W Hz−1. These radio and optical luminosities are typical for wide-angle tailed radio galaxies near the borderline between Fanaroff–Riley classes I and II. The projected largest angular size of ≈8 arcmin corresponds to 800 kpc and the full length of the source along the curved jets/trails is 1.1 Mpc in projection. X-ray data from the XMM–Newton archive yield an upper limit on the X-ray luminosity of the thermal emission surrounding RGZ J082312.9+033301 at 1.2–2.6 × 1043 erg s−1 for assumed intracluster medium temperatures of 1.0–5.0 keV. Our analysis of the environment surrounding RGZ J082312.9+033301 indicates that RGZ J082312.9+033301 lies within a poor cluster. The observed radio morphology suggests that (a) the host galaxy is moving at a significant velocity with respect to an ambient medium like that of at least a poor cluster, and that (b) the source may have had two ignition events of the active galactic nucleus with 107 yr in between. This reinforces the idea that an association between RGZ J082312.9+033301 and the newly discovered poor cluster exists.